The Effect of Blended Learning Model on Students' Learning Outcomes and Learning Independence for Contact Lens Courses At YLPTK Padang Optical Refraction Academy - Rina Novalinda; Febry Corina (Universitas Muhammadiyah Enrekang, 2025)
This study aims to determine the effect of blended learning model on learning outcomes and learning independence of students in the Contact Lens course at the YLPTK Padang Optical Refraction Academy. The research design used a quasi-experimental approach with a control group (using conventional learning methods) and an experimental group (using a blended learning model), each consisting of 30 students. The learning outcome measurement instrument was an objective test that had been tested for validity and reliability. Data were analyzed descriptively and inferentially with a paired t-test and independent samples t-test at a significance level of α = 0.05. The results of the descriptive analysis showed that the average posttest score of the experimental group (M = 85.20; SD = 6.15) was higher than the control group (M = 74.35; SD = 7.02). Independent samples t-test confirmed a significant mean difference between the two groups (t(58) = 6.23; p < 0.001), while the paired t-test in the experimental group showed a significant increase in learning outcomes from pretest to posttest (t(29) = 12.47; p < 0.001). Based on the results of the analysis and development of the blended learning model, the following conclusions were obtained: There are differences in student learning outcomes for contact lens courses using the Blended learning model with the direct learning model. There are differences in student learning independence for contact lens courses using the Blended learning model with the direct learning model and there is an interaction between student learning outcomes and learning independence for contact lens courses in the Blended Learning model and the direct learning model. These findings indicate that the application of blended learning is effective in improving students' understanding of concepts and clinical skills in the Contact Lens course. Based on these results, it is recommended that the YLPTK Padang Optic Refraction Academy integrate the blended learning model more broadly to support the optimization of the clinical learning process and improve the achievement of student learning outcomes.